The effect of firearms in inducing stress in high school students in the city of Düzce (Turkey) - (:unkn) unknown (Turkish Association of Nervous and Mental Health, 2009)
Objective: This study aimed to examine the behaviors of high school students exposed to firearms and firearmsrelated violence, which they had perpetrated or witnessed, and whether or not these events were related to stress. Method: The study was conducted in Düzce province, which is characterised by the widespread use of firearms. A questionnaire was prepared to ascertain students' attitudes and behaviors towards owning firearms, their thoughts about firearms- related violence, and whether or not they had been a victim or witness to firearmsrelated violence. After a stress level scale was added to the questionnaire, it was administered to 791 students randomly chosen from the 8304 students that were attending all high schools in Düzce. The results were evaluated with using SPSS v.11.0 software. Results: The level of stress in students that had contact with firearms, whether or not they were faced with a violent act, may be reached the adaptation difficulty level. Aggressive behaviors like hectoring occurred between coequal groups and brothers/sisters, affectedstress levels. Exposure to and witnessing violent acts had important roles on level of stress. Gender, income level, and lack of a private room at home for adolescents affected stress levels. Contrary to expectations, the presence of firearms at home or in their surroundings did not have an effect on stress levels. Hearing the sound of gunfire was one of the most important factors related to stress levels. Conclusion: Because of its ability to induce stress in adolescents, they must be protected form exposure firearms and their use, which is widespread in Düzce.
Keywords: Adolescence; Firearms; Stress